Aza-Reformatsky Reaction Promoted by Catalytic Samarium Diiodide: Synthesis of β-Amino Esters or Amides - Rodríguez-Solla, Humberto; Díaz-Pardo, Ainhoa; Concellón, Carmen; del Amo, Vicente (Synlett, 2014)
The synthesis of β-amino esters or amides has been achieved from moderate to high yields from the reaction of imines and α-halo esters or amides promoted by catalytic amounts of samarium diiodide in the presence of magnesium turnings as co-reductant. A mechanism is proposed to explain this catalytic samarium(II)-promoted aza-Reformatsky reaction.
Keywords: amino esters; catalytic reactions; enolates; Reformatsky reaction; samarium